Hadith #1454 - Sunan al-Nasa'i - Abdur-Razzaq عبد الرزاق بن همام; al-'Ala' bin al-Hadrami; al-Sa'ib bin Yazid bin Akht Namr; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ibn Jurayj ابن جريج; Isma'il bin Muhammad bin Sa'd إسماعيل بن محمد بن سعد بن أبي وقاص الزهر; Muhammad bin 'Abdul Malik bin Zunjwiya محمد بن عبد الملك بن زنجويه الغزال (Sunan al-Nasa'i)
“Uthman prayer four (rak’ahs) in Mina until news of that reached ‘Abdullah who said: ‘I prayed two rak’ahs with the Messenger of Allah (ﷺ).'”
Grade:

Hadith #2893 - Sunan al-Nasa'i - Abdur-Razzaq عبد الرزاق بن همام; Anas ibn Malik; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Muhammad bin 'Abdul Malik bin Zunjwiya محمد بن عبد الملك بن زنجويه الغزال; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan al-Nasa'i)
“The Prophet said: “There are five animals all of which are vermin, and may killed outside and inside the sanctuary: Vicious dogs, crows, kites, scorpions and mice.'”
Grade: